The poetics of cruising : queer visual culture from Whitman to Grindr - Parlett, Jack, 1992- (University of Minnesota Press, 2022)
"A groundbreaking new history of urban cruising through the lenses of urban poets The Poetics of Cruising explores the relationship between cruising, photography, and the visual in the work of leading poets, from Walt Whitman in the nineteenth century to Eileen Myles in the twenty-first. What is it that happens, asks Jack Parlett, and what is it that is sought, in this often transient moment of perception we call cruising, this perceptual arena where acts of looking between strangers are intensified and eroticized? Parlett believes that this moment is not only optical in nature but visual: a mode of looking that warrants comparison with the ways in which we behold still and moving images. Whether it's Whitman's fixation with daguerreotypes, Langston Hughes's hybrid photographic works, or Frank O'Hara's love of Hollywood movie stars, argues Parlett, the history of poets cruising abounds with this intermingling between the verbal and the visual, the passing and the fixed. To look at someone in the act of cruising, this history suggests, is to capture, consider, and aestheticize, amid the flux and instantaneity of urban time. But it is also to reveal the ambivalence at the heart of this erotic search, where power may be unevenly distributed across glances, and gendered and racialized bodies are marked. Thus, in identifying for the first time this confluence of cruising, poetry, and visual culture, Parlett concludes that the visual erotic economy associated with gay cruising today, exemplified by the photographic grid of an app like Grindr, is not a uniquely contemporary phenomenon. Innovative, astute, and highly readable, and drawing on compelling archival material, The Poetics of Cruising is a must for scholars of queer and LGBTQ literature and culture, modern and contemporary poetry, visual studies, and the history of sexuality"--